2021
DOI: 10.1007/s00259-021-05243-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravital microscopy of tumor vessel morphology and function using a standard fluorescence microscope

Abstract: Purpose The purpose of the study was to demonstrate the performance and possible applications of an intravital microscopy assay using a standard fluorescence microscope. Methods Melanoma and pancreatic ductal adenocarcinoma xenografts were initiated in dorsal window chambers and subjected to repeated intravital microscopy. The entire tumor vasculature as well as the normal tissue surrounding the tumor was imaged simultaneously with high spatial and tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Peng Si et al describe that label-free optical coherency tomography technology has been applied by advanced novel optical designs and algorithms, enabling optical coherency tomography to detect tumor margins and blood vessels more accurately [ 43 ]. Jon-Vidar Gaustad et al showed that a dorsal window model in mice allowed simultaneous MRI imaging to reflect vascular morphology and function within the tumor microenvironment [ 44 ].…”
Section: Technical Methods Of In Vivo Imagingmentioning
confidence: 99%
“…Peng Si et al describe that label-free optical coherency tomography technology has been applied by advanced novel optical designs and algorithms, enabling optical coherency tomography to detect tumor margins and blood vessels more accurately [ 43 ]. Jon-Vidar Gaustad et al showed that a dorsal window model in mice allowed simultaneous MRI imaging to reflect vascular morphology and function within the tumor microenvironment [ 44 ].…”
Section: Technical Methods Of In Vivo Imagingmentioning
confidence: 99%
“…In a murine model of non-Hodgkin lymphoma, tissue clearing revealed that the delivery of therapeutic CD20 fragment antigen-binding (FAB) antibody regions was dependent on tumor perfusion ( 164 ). IVM showed that preserving endosteal vessels in AML improves the efficacy of chemotherapy ( 123 ).…”
Section: Volume Imaging As a Platform For Therapy Developmentmentioning
confidence: 99%
“…Currently, DSWC can also be applied to fluorescence and photoacoustic imaging, ultrasound, magnetic resonance imaging (MRI), positron emission tomography (PET) imaging, and multimodal imaging. 27,29,30 Many studies on DSWC have shown the structural and functional differences between tumor blood vessels and normal blood vessels and can quantitatively study tumor blood vessels and normal blood vessel permeability, hemoglobin saturation, and other parameters. In addition, DSWC models enable us to further understand the microcirculation and metabolism of tumors and study living animals at the cellular and molecular levels.…”
Section: Introductionmentioning
confidence: 99%